Sex-Based Heterogeneity in the Clinicopathological Characteristics and Prognosis of Breast Cancer: A Population-Based Analysis - Han, Yiqun; Wang, Jiayu; Wang, Zijing; Xu, Binghe (Frontiers in Oncology, 2021)
Purpose: To better understand the differences in clinicopathological features and prognosis between male breast cancer (MBC) and female breast cancer (FBC). Material and Methods: Data on patients diagnosed with breast cancer from January 1, 2010 to December 31, 2016, were obtained from the Surveillance, Epidemiology, and End Results database. Selected patients were classified into MBC and FBC, of which population demographics and clinicopathological features at baseline were successively extracted for analysis. Comparative analysis was performed to explore the differences in baseline characteristics, followed by propensity-score matching to calibrate the objective distinctions for adjusted analysis. Survival analysis was carried out to investigate divergences presented in prognosis from the two cohorts, and risk factors for prognosis were successively identified using univariate and multivariate Cox analyses. Results: A total of 407341 individuals were eligible, including 3111 MBC (0.7%) and 404230 FBC (99.3%) patients. Comparatively, patients with MBC tended to be older at diagnosis, with a higher confirmation of ductal carcinoma, a higher histological grade, a higher TNM stage, a higher proportion of luminal-like subtype, a higher rate of lung metastasis, a lower incidence of liver involvement, and a lower rate of surgical, radiation, and chemotherapeutic delivery. The overall prognosis of MBC was significantly worse than that of FBC, with a decreasing divergence both in median overall survival (65.5 months vs. 72.7 months, P<0.0001) and median breast cancer-specific survival (75.4 months vs. 77.8 months, P<0.0001). However, these discrepancies were not consistent among patients from different subgroups stratified by molecular subtype, age at diagnosis, or disease stage. Conclusion: In this study, sex-based heterogeneity in clinicopathological characteristics and prognostic profiles was observed in the overall population of patients with breast cancer and was significantly variable among different subgroups. A male-specific design with reasonable endpoints for a clinical trial protocol will be warranted in the future.